FORMATION ACCOUNTING IN UNIVERSITIES. ACCOUNTANT ROL IN MYPES WITHIN THE ACTUAL CONTEXT - Palomino Silva, Julio Andrés (2010)
The divorce between theory given in the university classroom and actual practice of a university career is a reflection of the gap between academia and reality, and if this situation we add the effect of global recession and the spread of higher education, we find a university that necessarily needs to be renewed and adapted to the needs and challenges. In our country, one way to tackle the international context of economic recession have been the MSEs that with regard to issues such as employment generation, improving competitiveness, including cooperation and partnerships, export promotion and above all the growth of our country are a key element, but in recent times has been characterized by a scenario unfold in changing and unstable. In this situation, it is important consider that the counter receives training in college to play an appropriate role in the MSEs. The conclusion of this interesting review is that the constraints facing the counter and preventing potential exploit within the MSEs are rooted in the dislocation between the university and current socio-economic.